Descent groups among cognatic societies: the Dusun tribes of Inland Sabah/North Borneo - Sanen Marshall; Veronica Petrus Atin; Low, Kok On; Lim, Alice; Nelson Adeh (American Scientific Publishers, 2016)
In the following discussion, the authors present a comparison of various societies in Borneo which includes for the first time a society that features descent groups. The claim that the Dusun society of the Upper Labuk River in inland North Borneo or Sabah possesses descent groups is one that has yet to be acknowledged in the wider Borneo literature. Descent groups are typically representative of some form of lineally ordered kinship system. Claims that unilineal or ambilineal kinship systems might exist in Borneo have been greeted with little interest, with caution or sometimes with outright rejection. By comparing the social groups produced by the Dusun society of the Upper Labuk River against the social groups produced by the more typical cognatic societies of Borneo, we are putting forward the claim that kinship systems are, at least in this region, a matter of great importance to the kind of social groups that are subsequently produced. The authors are not, however, claiming that lineally ordered kinship systems are in and of themselves able to produce structurally stable groups. Although the following discussion does necessarily refer to one model of tribal organisation derived from a lineally ordered society in Africa, it goes on to show that the lineally ordered Dusun tribes of Borneo were uniquely a product of local arrangements established for the purpose of accommodating a native customary law prohibiting marriages between close cousins.